1994
DOI: 10.1083/jcb.124.5.783
|View full text |Cite
|
Sign up to set email alerts
|

PCM-1, A 228-kD centrosome autoantigen with a distinct cell cycle distribution

Abstract: Abstract. We report the identification and primary sequence of PCM-1, a 228-kD centrosomal protein that exhibits a distinct cell cYcle-dependent association with the centrosome complex. Immunofluorescence microscopy using antibodies against recombinant PCM-1 demonstrated that PCM-1 is tightly associated with the centrosome complex through G~, S, and a portion of G2. However, late in G2, as cells prepare for mitosis, PCM-1 dissociates from the centrosome and then remains dispersed throughout the cell during mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
124
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 24 publications
11
124
0
Order By: Relevance
“…In lanes 7-14 the relative strength of binding of the two probes is tested by competition with increasing concentrations of unlabelled probe corresponding to the opposite allele of rs208747 (molar excesses of competitor were 1-, 10-, 20-and 50-fold). A band is visible in lane 7 but not in lanes [8][9][10]. Similarly a band is visible in lanes 11 and 12 but not in lanes 13 and 14.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In lanes 7-14 the relative strength of binding of the two probes is tested by competition with increasing concentrations of unlabelled probe corresponding to the opposite allele of rs208747 (molar excesses of competitor were 1-, 10-, 20-and 50-fold). A band is visible in lane 7 but not in lanes [8][9][10]. Similarly a band is visible in lanes 11 and 12 but not in lanes 13 and 14.…”
Section: Discussionmentioning
confidence: 71%
“…Dissociation occurs during mitosis when PCM1 is dispersed throughout the cell. 10 Immunolabelling studies performed by Kubo et al 11 found that PCM1 was present in centriolar satellites and in electron dense granules between 70 and 100 nm in diameter. These were originally thought to be scattered only around the centrosomes, but further studies proved that PCM1 was also found throughout the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MTUS1 gene is a newly identified candidate tumor suppressor gene [14] and the protein product of this gene has been shown to interact with angiotensin II AT2 receptor, and inhibit growth-factor-induced extracellular-regulated kinase (ERK) activation and cell proliferation [25,26]. The protein product of PCM1 gene is a centrosomal protein that exhibits a distinct cell cycle-dependent association with the centrosome complex [27], and has been showed to form fusion protein with RET protooncogene in papillary thyroid carcinoma [28], and with JAK2 in leukemia [29]. The protein product of LZTS1 contains a leucine zipper region with similarity to the DNA-binding domain of the cAMP-responsive activating transcription factor-5, and may involve in cell cycle regulation at late S-G2/M stage [30].…”
Section: Resultsmentioning
confidence: 99%
“…One component is PCM1, a 228-kDa autoantigen recognized by anti-centrosome serum 4,8 . PCM1 has a dynamic cellular distribution, localizing with centrosomal satellites throughout the cell cycle except during metaphase and anaphase, when it becomes cytosolic 8,9 .…”
mentioning
confidence: 99%